Three-hourly gridded volcanic ash emissions for the Eyjafjallajökull 2010 eruption ... - Brodtkorb, André Rigland; Valdebenito, Alvaro; EEMEP Contrubutors (Zenodo, 2020)
Forward simulations of the Eyjafjälla 2010 eruption with unit emissions. These files are used to create an emission estimate of a volcanic eruption. Each file corresponds to an individual emission time point, and contains 19 individual emission simulations. Each emission simulation emits 1 teragram of ash into a unique vertical level of the model. The levels are labeled L01 .. L19, and designate level number from the top of the atmosphere (top of level 1 is close to 130 hPa or around 14 km ASL). The hybrid sigma levels are defined in Vertical_levels_22_650m.txt. The files were created using eEMEP Unimod_ASH compiled by Alvaro Valdebenito (module cams50/201809) on the Nebula supercomputer. ... : Data and products are licensed under Norwegian license for public data (NLOD) and Creative Commons 4.0 BY Internasjonal (see https://www.met.no/en/free-meteorological-data/Licensing-and-crediting for details). Credit should be given to The Norwegian Meteorological institute, shortened "MET Norway", as the source of data. Some suggestions: «Data from The Norwegian Meteorological Institute», «Based on data from MET Norway». ...